Characterization of the complete chloroplast genome of Salix magnifica, a vulnerable species endemic to China. Issue 3 (2nd July 2020) - Liu, Jinfeng; Liu, Siyan; Wang, Rui; Guan, Shuyan; Qu, Jing
Abstract: Salix magnifica is only sporadically distributed in the western part of Sichuan, the area of the willows is narrow. There are not many plants, and they easily fall into the endangered state. It is currently on the International Union for Conservation of Nature (IUCN) red list of threatened species. In this study, we first assembled the complete chloroplast (cp) genome of Salix magnifica by Illumina paired-end reads data. The whole genome was 154, 977 bp, consisting of a pair of inverted repeats of 27, 457 bp, large single-copy region, and a small single-copy region (71, 119 and 16, 205 bp in length, respectively). The cp genome contained 116 genes, including 80 protein-coding genes and 36 tRNA genes. The overall GC content of the whole genome was 36.7%. A neighbour-joining phylogenetic analysis demonstrated a close relationship between Salix magnifica and Salix oreinoma .